How trade policies starve healthy diets - Roy, Devesh; Sharma, Manika (2019)
A recent Lancet study regards dietary factors to be amongst the biggest risk factors for death and disability in India. Healthier, safer and more nutritious diets are keys to fighting high levels of under-nutrition and rising levels of obesity in India.